ANALISIS GAYA BELAJAR SISWA KELAS III PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR NEGERI 15 KARTIASA TAHUN AJARAN 2023-2024 - Fitriani; Topik; Elsa Mulya Karlina (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research began with the discovery of the phenomenon of students who have different learning styles from one student to another in class III in Indonesian language lessons. The objectives of this research are (1) to describe students' auditory learning styles in understanding Indonesian language lesson material for class III at SD Negeri 15 Kartiasa; (2) Describe students' visual learning styles in understanding Indonesian language lesson material for class III at SD Negeri 15 Kartiasa; and (3) Describe how students' kinesthetic learning styles are in understanding Indonesian language lesson material for class III at SD Negeri 15 Kartiasa. his research uses a qualitative approach with a phenomenological type of research. Data collection techniques in this research used interview, observation and documentation techniques. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Data validity checking techniques use source triangulation and member checking. The results of this research show that class III students in Indonesian language subjects have the following auditory learning style: (1) students read by making sounds, some softly and some loud or loud, (2) students listen to what the teacher says. when explaining the material in front, (3) Students like to study alone rather than in groups. Next, the visual learning style is (1) Students like to learn using drawing media, (2) Students like to read books with pictures, (3) Students draw using colorful markers, (4) Students like to learn using mind mapping, 5) students write using blacak and blue pens. Then the kinesthetic learning style is: (1) students like to learn to move their fingers when reading as a guide, (2) students like to learn while walking to the right and left during the learning process, and (3) students like to follow and practice the movements of the singing material or story.